Perspektif Hak Asasi Manusia Terhadap Terpidana Hukuman Mati Menurut UU Nomor 1 Tahun 2023 Tentang KUHP - Sayafrizal Sayafrizal; Annisa Suryani Putri (DOKTRINA: JOURNAL OF LAW, 2023)
This article will discuss human rights from the perspective of law number 1 of 2023 concerning the criminal code and the death penalty mechanism in Indonesia. This research method is a qualitative literature study method by collecting both primary and secondary library sources. The death penalty as a special type of crime in the new Criminal Code is regulated from Article 98 to Article 102. The reforms that have been carried out in the new Criminal Code, the judge imposes the death penalty with a probation period of 10 years. This is contained in Article 100 of Law Number 1 of 2023 concerning the Criminal Code. Article 100 paragraph (1) of the Criminal Code stipulates that the judge imposes the death penalty with a probation period of 10 years by taking into account the defendant's feelings of remorse and the hope of improving himself or the defendant's role in the crime. In Article 100 paragraph (2) it is explained that the death penalty with a probationary period as intended in paragraph (1) must be included in the court decision. then when he shows commendable attitudes and actions during the probation period, the death penalty can be changed to life imprisonment.